Anaerobic mono-digestion of pig manure in a leach bed coupled with a methanogenic reactor: Effects of the filter media. (10th October 2019) - Yang, Jie; Wang, Dehan; Luo, Zifeng; Zeng, Weishen
Abstract: This work pioneered the efficient coupling of a leach bed reactor (using a filter medium and no anaerobic sludge) and a continuous stirred-tank reactor (LBR-CSTR) to perform the anaerobic mono-digestion of pig manure. The leachate residue of the pig manure (LR-PM) was dried by a biodrying process. The results revealed that the LBR-CSTR (with ceramsite (C) as the filter medium) showed the best performance (the biogas production was 241.68 ml/g volatile solids (VS), which was 1.24 times higher than that of the control CSTR (CK)), the weight loss of pig manure was the highest (the reduction was 95.83%), and the organic degradation was 86.82% (which was 19.49% higher than that of the CK). The seed germination index (GI) was higher than 50%, and the clogging of the leach bed was overcome. The energy and resource utilizations of pig manure were readily achieved. Graphical abstract: Image 1 Highlights: Mono-digestion of pig manure was performed in LBR-CSTR. Use ceramic as a filter media overcome the clogging of pig manure in LBR. Addition of biogas slurry promoted hydrolytic acidification from pig manure. Pig manure decreased by 2.3 kg, reduction is 95.83% after digestion. Leachate residue of pig manure can use as base fertilizer.